SURVIVAL STRATEGIES OF TRADITIONAL MARKET TRADERS AGAINST DIGITAL ECONOMY MARKET COMPETITION IN MEDAN - Tri Utami Salsabila; Dinda Trikania; Muhammad Iqbal Asy'ari Lubis; Rizka Sabila Ritonga (Academic Solution Publisher, 2024)
Pasar Petisah Medan, as one of the active traditional markets. This market has faced major challenges since the end of 2019 when the outbreak of covid 19 resulted in the emergence of online markets. Consumers have experienced changes in shopping patterns that have led to a decrease in the turnover of traders in this market. This research aims to analyze the survival strategies applied by traditional traders in Pasar Petisah, Medan, in the face of competition with digital markets. Using a descriptive qualitative approach, this research examines the challenges faced by merchants, including economic conditions, market policies, and environmental changes that affect the sustainability of their businesses. The research subjects consisted of grocery merchants who are still actively selling at the location, while the object of the research included the strategies they implemented to survive amidst the changing market dynamics. The results of the study are expected to provide insight into the effectiveness of the strategies used by traders, as well as a contribution in formulating policies that support the development of Usaha Mikro, Kecil dan Menengah (UMKM) in traditional markets. This research also aims to increase understanding of the importance of digital transformation for the sustainability of traditional markets.